Clinical development and proof of principle testing of new regenerative vascular endothelial growth factor-D therapy for refractory angina: rationale and design of the phase 2 ReGenHeart trial - Leikas, Aleksi J.; Hartikainen, Juha E. K.; Kastrup, Jens; Mathur, Anthony; Gyöngyösi, Mariann; Fernández-Aviles, Francisco; Sanz-Ruiz, Ricardo; Wojakowski, Wojtek; Gwizdała, Adrian; Luite, Riho; Nikkinen, Marko; Qayyum, Abbas A.; et al. (BMJ PUBLISHING GROUP, 2025)
Background Despite tremendous therapeutic advancements, a significant proportion of coronary artery disease patients suffer from refractory angina pectoris, that is, quality-of-life-compromising angina that is non-manageable with established pharmacological and interventional treatment options. Adenoviral vascular endothelial growth factor-D Delta N Delta C (AdVEGF-D)-encoding gene therapy (GT) holds promise for the treatment of refractory angina.
Methods ReGenHeart is an investigator-initiated, multicentre, randomised, placebo-controlled and double-blinded phase 2 clinical trial that aims to study the safety and efficacy of intramyocardially administered angiogenic AdVEGF-D GT for refractory angina. Patients will be randomised in a 2:1 ratio and blocks of six to receive either AdVEGF-D or placebo. Primary endpoints are improvements in functional capacity assessed with the 6 min walking test and angina symptoms with Canadian Cardiovascular Society class after 6 month follow-up. Secondary endpoints are improvements in myocardial perfusion assessed with either positron emission tomography or single-photon emission CT after 6 month follow-up and functional capacity and angina symptoms after 12 months. In addition, changes in the quality of life, the use of angina medication and the incidence of major adverse cardiac and cerebrovascular events will be evaluated.
Conclusions The phase 2 ReGenHeart trial will provide knowledge of the safety and efficacy of AdVEGF-D GT to ameliorate symptoms in refractory angina patients, extending and further testing positive results from the preceding phase 1/2a trial.